Fundamentals of Child Rights - VERMA, PUSHPA LATA (THE PRIMARY TEACHER, 2015)
India is home to about four hundred and forty million children, that is, 42 per cent of the total population. They are our most valuable asset and a significant human resource. The prosperity of our country depends indeed in their holistic development, that is, physical, mental, social and economic development. India has adopted various child-friendly policies, laws and programmes for the allround development of children. We have the National Policy for Children which obligates on the State to provide adequate services to children for their full physical, mental and social development. The National Charter for Children emphasises the Government of India’s commitment to children’s rights to survival, health and nutrition, standard of living, play and leisure, early childhood care, education, protection of the girl child, right to a family and right to be protected from economic exploitation and all forms of abuse. The National Commission for Protection of Child Rights has been set up by an Act of Parliament in 2007 for proper enforcement of children’s rights and effective implementation of laws and programmes relating to children. Several States in the country have also set up similar Commissions. There is no issue more vital to humanity and its future than enabling children to realise their full potential. The needs and the rights of the children all around the world must be accorded top priority in all developmental efforts